Interaction between BDNF Polymorphism and Physical Activity on Inhibitory Performance in the Elderly without Cognitive Impairment - Canivet, Anne; Albinet, Cédric T.; Rodríguez-Ballesteros, Montserrat; Chicherio, Christian; Fagot, Delphine; André, Nathalie; Audiffren, Michel (Frontiers in Human Neuroscience, 2017)
Background: In the elderly, physical activity (PA) enhances cognitive performances, increases brain plasticity and improves brain health. The neurotrophic hypothesis is that the release of brain-derived neurotrophic factor (BDNF), which is implicated in brain plasticity and cognition, is triggered by PA because motoneurons secrete BDNF into the bloodstream during exercise. Individual differences in cognitive performance may be explained by individual differences in genetic predisposition. A single nucleotide polymorphism on the BDNF gene, BDNFVal66Met, affects activity-dependent BDNF secretion. This study investigated the influence of the BDNFVal66Met polymorphism on the relationship between PA and controlled inhibition performance in older adults. Methods: A total of 114 healthy elderly volunteers (mean age = 71.53 years old) were evaluated. Participants were genotyped for the BDNFVal66Met polymorphism. We evaluated inhibitory performance using choice reaction times (RT) and error rates from a Simon-like task and estimated their PA using two self-reported questionnaires. We established 4 groups according to PA level (active vs. inactive) and BDNFVal66Met genotype (Met carriers vs. Val-homozygous). The results were analyzed using ANOVA and ANCOVA, including age, gender and, body mass index as covariates. Results: The BDNFVal66Met polymorphism interacted with PA on controlled inhibition performance. More specifically, inactive Val-homozygous participants exhibited a lower inhibition performance than active Val homozygotes and inactive Met carriers; the former had a higher error rate without differences in RT. Conclusions: Differences between individuals on inhibitory performance may be partially understood by the interaction between genetic influence in BDNF secretion and PA level. The results of this study clearly support the neurotrophic hypothesis that BDNF synthesis is an important mechanism underlying the influence of physical activity on brain structure and functions.